Temperature behavior of water and n-decane bound to nanosilica or poly(methylsiloxane) - V. V. Turov; T. V. Krupska; M. D. Tsapko; V. M. Gun'ko (Хімія, фізика та технологія поверхні, 2015)
The phase transition of n-decane bound to nanosilica initial hydrophilic or modified hydrophobic and branched 3D poly(methylsiloxane), PMS, was analyzed using 1H NMR and quantum chemical methods. Freezing and melting points of n-decane are affected by nanosilica or PMS in CDCl3 able to dissolve decane. The behavior of mixed water and decane depends on the adsorbent texture and surface nature, content of salt microparticles or nanoparticles and co-adsorbates. The freezing point depression under confined space results in stronger changes in the behavior of adsorbed decane than effects of melting delay occurring due to kinetic suppression and immobilization of solid-like structures in mesopores. The dispersion media (nonpolar CCl4, weakly polar CDCl3, polar CD3CN and trifluoroacetic acid) influence the interfacial and temperature behavior of mixed water and n-decane because decane can be easily dissolved in nonpolar or weakly polar solvents but water can strongly interacts with polar solvents and polar solid particles.